Effects of Substrate Media on Growth and Yield of Curl Leaf Kale - Sombatsri, Prapatsorn (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
The objective of this research was to study the effects of growing media on the growth and yield of curly kale. The experiment was designed using a Completely Randomized Design (CRD) with 9 treatments and 4 replications as follows: 1) Sandy loam soil: cow manure at a ratio of 1:2, 2) Sandy loam soil: coconut coir: cow manure at a ratio of 1:1:2, 3) Sandy loam soil: raw rice husk: cow manure at a ratio of 1:1:2, 4) Sandy loam soil: raw rice husk: coconut coir: cow manure at a ratio of 1:1:1:2, 5) Sandy loam soil: pig manure at a ratio of 1:1, 6) Sandy loam soil: coconut coir: pig manure at a ratio of 1:1:1, 7) Sandy loam soil: raw rice husk: pig manure at a ratio of 1:1:1, 8) Sandy loam soil: raw rice husk: coconut coir: pig manure at a ratio of 1:1:1:1, 9) Sandy loam soil: coconut coir: cow manure: raw rice husk: 16-16-16 fertilizer at a ratio of 1:2:1:1:0.25. The results demonstrated that Treatment 2 yielded the highest growth of curly kale, as indicated by plant height, canopy width, number of leaves, and leaf width and length, measuring 10.13 cm, 21.17 cm, 6.67 leaves, 14.00 cm, and 8.83 cm, respectively. Additionally, it produced the highest fresh weight of the entire plant with roots at 33.84 grams, along with a root weight of 31.85 grams. Therefore, the growing media comprising a mixture of sandy loam soil, coconut coir, and cow manure in a ratio of 1:1:2 was determined to be the most suitable for cultivating curly kale.